2006
DOI: 10.1207/s15326942dn2901_2
|View full text |Cite
|
Sign up to set email alerts
|

Alphabetic Skills in Preschool: A Preliminary Study of Letter Naming and Letter Writing

Abstract: Development of letter naming and writing (skills in writing first name, dictated and copied letters, and dictated and copied numbers) was examined in 79 preschool children (M age = 56 months). Skills were assessed in the fall to determine the status of these procedural skills that are components of alphabetic knowledge at the start of the school year. Children with high letter-naming scores also had high scores on letter writing, including dictated or copied letters and writing some or all of the letters of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 17 publications
4
50
1
6
Order By: Relevance
“…In the dictation task, the number of letters handwritten was linked with letter knowledge, but not the quality of handwriting. This result is similar to that obtained by Molfese et al (2006) study, who found a link between letter naming and letter writing. Further studies are needed to better understand the link between perceptual and motor skills and the different components of handwriting.…”
Section: Discussionsupporting
confidence: 92%
“…In the dictation task, the number of letters handwritten was linked with letter knowledge, but not the quality of handwriting. This result is similar to that obtained by Molfese et al (2006) study, who found a link between letter naming and letter writing. Further studies are needed to better understand the link between perceptual and motor skills and the different components of handwriting.…”
Section: Discussionsupporting
confidence: 92%
“…Aun así, gracias a la fuerte relación existente entre lectura y escritura, cabe esperar que muchas de las variables detectadas como fundamentales en el aprendizaje de la lectura, lo sean también para la escritura (Shanahan, 2006). Efectivamente, Coker (2006) y Molfese, Beswick, Molnar & Jacobi-Vessels (2006) analizan en sus estudios la importancia del conocimiento del nombre de las letras y de la capacidad de deletrear palabras en el aprendizaje de la escritura, subrayando que su adquisición y dominio en 3-4 años se relaciona positivamente con una más tardía capacidad de escribir el propio nombre, letras y números bajo dictado. Así mismo, Sulzby, Barnhart & Hieshima (2001) destacan la importancia de unas primeras formas de dibujos, de la capacidad de deletrear palabras inventadas y del conocimiento del nombre de las letras en el desarrollo de las primeras habilidades de escritura en niños de 4-5 años.…”
Section: Antecedentesunclassified
“…Observation forms used in other studies to evaluate the name writing skills of preschool children were analyzed (Bloodgood, 1999;Haney et al, 2003;Estabrook, 2013;Haney, 2002;Ho, 2011;Molfese et al 2006;Sulzby et al, 1989, Gerde et al, 2012. Items of the observation form were determined following the literature review.…”
Section: Observation Form For Preschool Name Writingmentioning
confidence: 99%